Clinical and Imaging Trends of Ankle Sprains in Al Kharj City - Talal Hani Abdullah Arab; Naif Mohammed Alqahtani; Khalid Hisham Alkhalidi; Mohammed Ibrahim Alsuway; Meshari Khalid Alhumaydani; Khalid H. Al-jabr; Nawaf Majed Alqahtani; Salman Bader Alhusaini; Khaled Humood Alhumaid; Abdulaziz Faisal Alyamni; Abdulaziz Fahad Alamer; Nasser Mohammed Albayyahi; et al. (International Journal of Biomedicine)
Background: When the ligaments supporting the ankle become excessively stretched or torn, it results in an ankle sprain. It can occur when you awkwardly put your weight down on your foot, step in a hole, or twist your ankle when jogging or walking. The present study aimed to determine the incidence of ankle sprains and trends in advanced imaging among residents of Al Kharj. Material and Methods: This study represents a cross-section starting from June 2024 to December 2024. An evaluation of the clinical presentation and imaging trends in patients with ankle sprains was collected from three hospitals in Al Kharj (King Khaled, Aflag General, and Prince Sattam bin Abdulaziz University Hospitals). The study included 69 patients (88.4% males and 11.6% females) of different age groups and sprain severity. The clinical data included patient demographics (age, sex), the side of injury, Saudi or non-Saudi nationality, the results of the physical examination, and the treatment options. Imaging data included CT, MRI, or X-ray. Results: The largest age group according to age distribution was 12–20 years (39.1%), followed by 21–29 years (20.2%) and 30–39 years (17.3%). Ankle sprains were caused by sports injuries in 40.6% of cases, falls in 23.2%, and walking-related accidents in 18.8% of cases (P=0.0240). Imaging procedures of different ankle sprain cases showed that X-ray was the most common (92.7%), followed by MRI (34.7%), and ultrasonography (17.3%) (P<0.0001). Our results showed that 17.3% of cases received no treatment, 53.6% received medical treatment and slab or crepe bandage, and 21.7% had medical treatment and slab or crepe bandage followed by physiotherapy. Additionally, 7.2% had surgery to repair a ligament injury after an MRI confirmed the diagnosis. Conclusion: Ankle sprains are more common in younger people. Most of the time, conservative initial treatment (watchful waiting) is a safe option for initial injury management.